Response of four local cassava accessions to bio-mulch application time - Suwitono, Bayu; Chozin, Muhamad Achmad; Guntoro, Dwi; Suwarto, Suwarto (Kultivasi, 2023)
Cassava (Manihot esculenta Crantz) is widely planted on marginal land with low soil fertility. During the initial growth phase, cassava often loses competition against weeds. Legume cover crops are widely used to increase soil fertility, prevent erosion, and suppress weeds. This study aimed to determine the effect of Arachis pintoi bio-mulch application time on the growth and yield of cassava. This study was conducted using a factorial randomized block design. The first factor was four cassava accessions: Ketan Malang, Genjah Bayam, IR Jonggol, and Mangu. The second factor was six levels of bio-mulch planting time: manual weeding (without bio-mulch applications), bio-mulch planting at the same time as cassava planting, and four, eight, and twelve weeks before cassava planting. The observations included plant height, stem diameter, number of tubers, tuber weight, tuber length, plant biomass, dry matter, and productivity. The results showed that all cassava accessions responded similarly to the planting time of A. pintoi bio-mulch. Different bio-mulch application time was insignificant in the cassava growth, except for the number of tubers and tuber diameter. The twelve weeks before cassava planting tends to reduce the results of cassava accessions.Keywords: Arachis pintoi, cover crop, dry land, growth, yield